2015
DOI: 10.1111/tpj.12790
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome atlas of the Arabidopsis funiculus – a study of maternal seed subregions

Abstract: These authors contributed equally to this manuscript. SUMMARYThe funiculus anchors the structurally complex seed to the maternal plant, and is the only direct route of transport for nutrients and maternal signals to the seed. While our understanding of seed development is becoming clearer, current understanding of the genetics and cellular mechanisms that contribute to funiculus development is limited. Using laser microdissection combined with global RNA-profiling experiments we compared the genetic profiles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Sucrose may be directly transported into seeds by sucrose transporters (SUT) (Weise et al 2000; Sauer 2007), without needing to be turned over into other forms, resulting in a linear correlation between sucrose and seed weight. A previous microarray study showed that AtSUT4 is highly expressed in the Arabidopsis funiculus (Khan et al 2015) and in our transcriptome data, BnSUT1, BnSUT4, BnSUT5, BnSUT6 , and other carbohydrate transporter genes BnGTP1, BnUTR2, BnPMT5, BnVGT1, BnPLT5 and BnPLT2 were also active in the B. napus funiculus (Fig. 6a).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Sucrose may be directly transported into seeds by sucrose transporters (SUT) (Weise et al 2000; Sauer 2007), without needing to be turned over into other forms, resulting in a linear correlation between sucrose and seed weight. A previous microarray study showed that AtSUT4 is highly expressed in the Arabidopsis funiculus (Khan et al 2015) and in our transcriptome data, BnSUT1, BnSUT4, BnSUT5, BnSUT6 , and other carbohydrate transporter genes BnGTP1, BnUTR2, BnPMT5, BnVGT1, BnPLT5 and BnPLT2 were also active in the B. napus funiculus (Fig. 6a).…”
Section: Discussionsupporting
confidence: 81%
“…1g) showed that the funiculus was ready to service the seed at a structural level. Previous histology studies revealed that the funiculi of B. napus (Chan and Belmonte 2013; Millar et al 2015), Arabidopsis (Belmonte et al 2013; Khan et al 2015), and Phaseolus vulgaris (Mawson et al 1994) showed proliferation of the vasculature tissue from the ovule to the globular stage, supporting transport as a primary function during seed filling. During the development of B. napus seed, the seed fresh weight increased nearly twofold during the morphogenesis phase from 7 to 21 DAF, and then continuously increased during seed filling from 21 to 35 DAF (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations